2019
DOI: 10.7567/1882-0786/ab6031
|View full text |Cite
|
Sign up to set email alerts
|

Mode-locked fiber laser at 2.8 μm using a chemical-vapor-deposited WSe2 saturable absorber mirror

Abstract: We demonstrate a 2.8 μm mid-infrared Er-doped ZBLAN mode-locked fiber laser by employing transition metal dichalcogenides (TMD) as a saturable absorber mirror (SAM) for the first time. The TMD-SAM with a large modulation depth of 24% was fabricated by transferring a chemical-vapor-deposited high-quality large-area few-layer WSe2 on a gold-coated mirror. Stable mode-locked pulses of 21 ps were obtained with a repetition rate of 42.43 MHz and an average output power up to 360 mW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In the next two years, Q-switched solid-state lasers in 3 m based on MoS and WSe were demonstrated by Zhang and Liu et al successively [ 276 , 277 ]. In 2020, Guo et al achieved mode-locked operation based on CVD-grown WSe SA mirror at 2789.6 nm with a maximum average output power of 360 mW and a repetition rate of 42.43 MHz, which is the first time TMD severed as mode-locker in the 3- m region [ 278 ].…”
Section: Applications Of 2d Materials In Ultrafast Lasersmentioning
confidence: 99%
“…In the next two years, Q-switched solid-state lasers in 3 m based on MoS and WSe were demonstrated by Zhang and Liu et al successively [ 276 , 277 ]. In 2020, Guo et al achieved mode-locked operation based on CVD-grown WSe SA mirror at 2789.6 nm with a maximum average output power of 360 mW and a repetition rate of 42.43 MHz, which is the first time TMD severed as mode-locker in the 3- m region [ 278 ].…”
Section: Applications Of 2d Materials In Ultrafast Lasersmentioning
confidence: 99%
“…Next, Guo et al fabricated a WSe 2 -SAM by the CVD technique in 2019, and realized a mode-locked pulse of 21 ps at 2790 nm in an Er 3+ :ZBLAN fiber laser, whose output power was up to 360 mW. [238] In 2021, Luo et al also reported a mid-IR mode-locked fiber laser based on gold nanowires. [239] Moreover, harmonic mode-locking phenomenon in 2.5-4 μm mid-IR fiber lasers based on metallic nanomaterial SAs were also realized in experiment.…”
Section: Passively Mode-locked Fiber Lasers In the 25-4 µM Region Usi...mentioning
confidence: 99%
“…fabricated a WSe 2 ‐SAM by the CVD technique in 2019, and realized a mode‐locked pulse of 21 ps at 2790 nm in an Er 3+ :ZBLAN fiber laser, whose output power was up to 360 mW. [ 238 ] In 2021, Luo et al. also reported a mid‐IR mode‐locked fiber laser based on gold nanowires.…”
Section: Status and Advances Of Mid‐ir Ultrafast Fiber Lasersmentioning
confidence: 99%
“…BP exhibits a large modulation depth but it is easy to oxidize in the ambient air. Despite graphene is characterized by zero bandgap, the modulation depth of single-layer graphene is only about 2.3% [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%